Critical capabilities for widening international new ventures' geographical scope. Issue 2 (April 2021) - Blesa, Andreu; Ripollés, María
Abstract: Current findings are still inconclusive with regard to the role played by the characteristics of social networks in INVs' early geographical scope. This study analyses how entrepreneurial-oriented networks affect new ventures' early geographical scope through critical capabilities. We have adopted a behavioural perspective to investigate the effect of social networks both on international new ventures' geographical scope and on their critical capabilities such as absorptive and adaptive capabilities. Results from a sample of 183 Spanish international ventures confirm the importance of entrepreneurial orientation as a network characteristic for early geographical scope. Additionally, the positive effect of adaptive capability on new ventures' early geographical dispersion has been confirmed but not so in the case of absorptive capabilities. Our results suggest that future research must be careful to assume international new ventures' absorptive capability as a prerequisite to their cross-border expansion.